1997
DOI: 10.1056/nejm199704243361703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cardiac Sympathetic Innervation on Coronary Blood Flow

Abstract: Increases in coronary blood flow in response to sympathetic stimulation correlated with the regional norepinephrine content in the cardiac sympathetic-nerve terminals. These findings suggest that cardiac adrenergic signals play an important part in regulating myocardial blood flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
145
5
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(158 citation statements)
references
References 38 publications
4
145
5
4
Order By: Relevance
“…Previous work has shown that sympathetic reinnervation contributes to partial restoration of exercise capacity 29 and plays a role for regulation of myocardial blood flow and metabolism. 30,31 In the present study, however, cardiac work, oxygen consumption, and efficiency at rest were not different between reinnervated and denervated transplant recipients. Additionally, there was no regional difference for contractile performance or oxygen consumption in reinnervated and denervated territories.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous work has shown that sympathetic reinnervation contributes to partial restoration of exercise capacity 29 and plays a role for regulation of myocardial blood flow and metabolism. 30,31 In the present study, however, cardiac work, oxygen consumption, and efficiency at rest were not different between reinnervated and denervated transplant recipients. Additionally, there was no regional difference for contractile performance or oxygen consumption in reinnervated and denervated territories.…”
Section: Discussioncontrasting
confidence: 67%
“…2,16 Whereas the exact mechanism by which this mixed humoral-nervous sympathetic stimulation mediates coronary vasodilation is unknown, activation of both ␤ 2 -adrenergic receptors on coronary smooth muscle cells and ␣ 2 -adrenergic receptors on endothelial cells with subsequent nitric oxide release has been suggested. 21,22 In our patients with ischemic heart disease, myocardial blood flow during sympathetic stimulation remained unchanged in the face of a 65% increase in cardiac work estimated by the rate-pressure product, and an increase in the coronary vascular resistance was recorded.…”
Section: Discussionmentioning
confidence: 99%
“…1 Impaired myocardial sympathetic innervation as in diabetic autonomic neuropathy or in the transplanted heart is associated with a reduced coronary vasodilatory response to sympathetic stimulation, whereas sympathetic reinnervation of the transplanted heart is associated with a normal coronary vasodilatory response. 2,3 In patients with coronary atherosclerosis and endothelial dysfunction, an abnormally augmented response to coronary ␣-adrenergic activation has been shown to result in a reduced coronary blood flow response during sympathetic stimulation. 4 -6 This phenomenon is believed to reflect a disturbance of the balance between coronary endothelial vasodilatory function and vasoconstrictor effects of myocardial sympathetic tone.…”
mentioning
confidence: 99%
“…In normal subjects, physiological hyperinsulinaemia can modulate central neural control directed to the heart by inducing vagal withdrawal paralleled by a slight sympathetic activation [26,27,28]. This dual action on the regional autonomic control could explain the overall increase of MBF, and the predominance of sympathetic innervation in the antero-septal ventricular wall [29] could account for the preferential increase of MBF in this region. Of interest, recent radionuclide studies have shown that signs of autonomic neuropathy are present at a very early stage in the heart of patients with diabetes, when microvascular complications are not yet clinically detectable [30].…”
Section: Discussionmentioning
confidence: 99%